2015
DOI: 10.3892/ol.2015.3651
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mutant p53 in oral squamous cell carcinoma is correlated with the effectiveness of intra-arterial chemotherapy

Abstract: Abstract. The aim of the present study was to evaluate the correlation between the positive expression rate of mutant p53 and the clinical characteristics of patients with oral squamous cell carcinoma (OSCC), as well as the effectiveness of intra-arterial chemotherapy. Expression of mutant p53 in tumor tissues was determined by immunohistochemical analysis of 51 OSCC patients, prior to and following intra-arterial chemotherapy. Prior to intra-arterial chemotherapy, mutant p53 positive rates in patients with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…Many researchers like Dragomir LP, Boslooper K, Geisler SA and Li Y had also concluded the same. 2,10,12,13 In the current study, p53 positivity was seen in 64% of the cases (percentage positive cells varying from 5-76% with mild, moderate and strong staining intensity and final score varying from 0 to 9 finds coherence with the work conducted by Franzman MB et al which has reported an immunoexpression of around 60percent. 8 The p53 positivity in cases of larynx and hypopharynx was relatively low (37%).…”
Section: It Plays An Important Role In Cell Cycle Control and Apoptosissupporting
confidence: 90%
See 1 more Smart Citation
“…Many researchers like Dragomir LP, Boslooper K, Geisler SA and Li Y had also concluded the same. 2,10,12,13 In the current study, p53 positivity was seen in 64% of the cases (percentage positive cells varying from 5-76% with mild, moderate and strong staining intensity and final score varying from 0 to 9 finds coherence with the work conducted by Franzman MB et al which has reported an immunoexpression of around 60percent. 8 The p53 positivity in cases of larynx and hypopharynx was relatively low (37%).…”
Section: It Plays An Important Role In Cell Cycle Control and Apoptosissupporting
confidence: 90%
“…This positive correlation has been commented upon by other researchers as well. 9 The same correlation between p53 positivity and lymph node mets was found to be statistically significant in oral cavity and oropharyngeal cases in concordance with the work done by researchers like Jain A et al and Li Y et al 13,14 However, Takes RP et al records an opinion about this correlation which is diametrically opposite. 18 The significance of p53 in having a relationship with lymph node metastasis is the most important prognostic factor for overall survival of HNSCC as about two-third of the patients with HNSCC who present with lymph node metastasis have a poor five year survival rates of 40-50%.…”
Section: It Plays An Important Role In Cell Cycle Control and Apoptosissupporting
confidence: 82%
“…Mutated p53 loses its ability to suppress the function of oncogenes. Furthermore, mutant p53 may function as an oncogene to stimulate cell division and promote the growth of tumor cells [6]. .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that mucositis and dysphagia were regarded to be inevitable but reversible 14, 32. Additionally, systemic toxicities such as anemia, thrombocytopenia and leukopenia were also reported before 60-62. Here, we summarized ten toxicities from the 34 studies, including oral diseases, mucositis, leukopenia, dermatitis, anemia, general condition, thrombocytopenia, nausea/vomiting, fever and hepatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%